2012
DOI: 10.1029/2011ja017496
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic ballooning/interchange instability in a bent plasma sheet

Abstract: [1] We use Time History of Events and Macroscale Interactions during Substorms (THEMIS) and GOES observations to investigate the plasma sheet evolution on 28 February 2008 between 6:50 and 7:50 UT, when there developed strong magnetic field oscillations with periods of 100 s. Using multispacecraft analysis of the plasma sheet observations and an empirical plasma sheet model, we determine both the large-scale evolution of the plasma sheet and the properties of the oscillations. We found that the oscillations ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 100 publications
(140 reference statements)
5
48
0
Order By: Relevance
“…A statistical study by Nowada et al (2009) showed that auroral electrojet indices reached higher values in the periods with smaller dipole tilt angles and thus, supported the idea by Kivelson and Hughes (1990) that larger number of smaller substorms occur in the periods of maximal dipole tilt. Additional evidence to revise the relationship between the substorm onset and tail configuration was provided by a number of case studies (e.g., Kubyshkina et al 2011;Sergeev et al 2011;Panov et al 2012, Ganushkina et al 2013, in which substorms were shown to be initiated in a curved magnetotail with excessively (due to additional external tilt) increased plasma sheet bending.…”
Section: Introductionmentioning
confidence: 99%
“…A statistical study by Nowada et al (2009) showed that auroral electrojet indices reached higher values in the periods with smaller dipole tilt angles and thus, supported the idea by Kivelson and Hughes (1990) that larger number of smaller substorms occur in the periods of maximal dipole tilt. Additional evidence to revise the relationship between the substorm onset and tail configuration was provided by a number of case studies (e.g., Kubyshkina et al 2011;Sergeev et al 2011;Panov et al 2012, Ganushkina et al 2013, in which substorms were shown to be initiated in a curved magnetotail with excessively (due to additional external tilt) increased plasma sheet bending.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the Cluster tetrahedron resolved the local (along the normal direction to the CS plane) gradients of magnetic field in flapping CS well but could not estimate variations in CS characteristics along the magnetotail. These variations, being weak in the mid-tail, should be stronger in the near-Earth region (see case studies in Nakamura et al, 2009;Panov et al, 2012a). The strong gradients of CS parameters along the x axis in this region are considered as potential drivers for CS instabilities resulting in flapping motion Pritchett and Coroniti, 2011;Panov et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…So far, estimates of the gradient ∂/∂X in the magnetotail have been obtained by using three independent approaches: (1) small-scale gradients of the near-Earth dipolarized CS can be estimated using direct measurements of Cluster mission in 2007(Nakamura et al, 2009 or THEMIS mission in the case of specific spacecraft configuration (Saito et al, 2010;Panov et al, 2012); (2) statistical investigation can give average profiles of the main CS parameters (B z component, plasma pressure and plasma density) along the tail (see statistics collected by AMPTE/IRM, Geotail and THEMIS spacecraft in Kan and Baumjohann, 1990;Wang et al, 2012); and (3) thermal electrons could be used as Published by Copernicus Publications on behalf of the European Geosciences Union. tracers of the magnetotail structure (Artemyev et al, 2011c).…”
Section: Introductionmentioning
confidence: 99%